Gambaran Pengetahuan Remaja Tentang Gejala – Gejala Awal Penyakit Menular Seksual di SMA Negeri 11 Makassar - Yenni Yenni; Andi Tenri Angka (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2018)
The aim of this research is to determine the description of adolescent knowledge about the early symptoms of sexually transmitted diseases based on the definition, early symptoms and types of STDs at SMA Negeri 11 Makassar. The type of research used was descriptive research, to determine adolescent knowledge about the early symptoms of sexually transmitted diseases at SMA Negeri 11 Makassar in 2018. The results of research conducted on 50 respondents at SMA Negeri 11 Makassar showed that there were 49 people (98 %) of respondents who answered correctly about the definition of sexually transmitted diseases, 47 people (94%) answered correctly about the symptoms of sexually transmitted diseases and 47 people (94%) answered correctly about the types of sexually transmitted diseases. From the results of the research the author draws the conclusion that adolescent knowledge based on the definition of sexually transmitted diseases is good with the highest percentage of 98%, based on the symptoms of sexually transmitted diseases is good with the highest percentage of 94%, based on the types of sexually transmitted diseases is good with the highest percentage of 94 %. It is recommended that students of SMA Negeri 11 whose level of knowledge is in the good category to be maintained and who are still lacking to motivate themselves to study and seek more information about sexually transmitted diseases.